Properties of Meromorphic Spiral-Like Functions Associated with Symmetric Functions. (28th August 2022) - Breaz, Daniel; Cotîrlă, Luminița-Ioana; Umadevi, Elangho; Karthikeyan, Kadhavoor R.
Abstract : To consolidate or adapt to many studies on meromorphic functions, we define a new subclass of meromorphic functions of complex order involving a differential operator. The defined function class combines the concept of spiral-like functions with other studies pertaining to subclasses of multivalent meromorphic functions. Inclusion relations, integral representation, geometrical interpretation, coefficient estimates and solution to the Fekete-Szegö problem of the defined classes are the highlights of this present study. Further to keep up with the present direction of research, we extend the study using quantum calculus. Applications of our main results are given as corollaries.